(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
Introduction: F-18 Fluorodeoxyglucose Positron Emission Tomography (18F-FDG PET/CT) is a hybrid non-invasive imaging tool that integrates PET and CT into a single imaging device. It is used to detect and measure metabolic activity in a cancer cell and, hence, can provide anatomic and metabolic information. 18F-FDG PET/CT is useful for the detection of loco-regional recurrence, distant metastases, and monitoring therapy response in patients with rectal carcinoma. This study was done to see the usefulness of 18F-FDG PET/CT in the follow-up evaluation of patients with rectal carcinoma. Materials and Methods: This retrospective study was done in the PET/CT division of the National Institute of Nuclear Medicine & Allied Sciences (NINMAS) between January 2021 and December 2022. A total of 26 patients with rectal carcinoma, requested for an F-18 FDG PET-CT scan were enrolled in this study. Image findings were analyzed and properly documented in a predesigned format to evaluate the results. Results: Total 26 patients with an average age of 47.69 and a follow up period of 6 months to 5 years were enrolled in this study. Histologically adenocarcinoma was seen in 21 patients, four patients were mucinous, two were papillary, and carcinoid tumor was found in one patient. On PET/CT imaging, no metastases were found in 17 (65.4%) out of 26 patients and metastases was seen in 9 (34.6%) patients. Among them four (44.5%) had lung, two (22.2%) had lymph nodes, one (11.1%) had liver and lymph node metastases, one (%11.1) had skeletal metastases, and one (11.1%) had peritoneal metastases. No significant association was observed with histopathology or treatment protocol. CEA was higher in patients with metastases and lower in those without. Conclusion: 18F-FDG PET/CT is an effective tool in follow up patients with rectal carcinoma as it can accurately detect locoregional recurrence or distant metastases. Bangladesh J. Nuclear Med. 25(2): 105-109, 2022